Development of Interactive Learning Multimedia Based on Google Site on the Sequence and Series Material for Grade XI IPA I Students of SMA Negeri 1 Tilango - Yusuf, Mayang R.; Abbas, Nurhayati; Ismail, Yamin (Universitas Ma'arif Lampung, 2024)
This research aims to produce interactive learning multimedia based on Google sites on sequence and series material in class XI IPA I SMA Negeri 1 Tilango with valid, practical and effective criteria. This research and development (Research and Development) uses the function D model, but its distribution is only carried out on a limited basis in research schools. The subjects in this research were class XI IPA I students at SMA Negeri 1 Tilango. The object of this research is interactive learning multimedia developed based on Google Sites in rows and rows. The results of the research were: (1) This learning multimedia has met the validity criteria because it has gone through the validation stage from 5 validators (5 media validators and 5 material validators). The average response obtained from media and material validators was